The roots of future rice harvests - Ahmadi, N.; Audebert, A.; Bennett, M. J.; Bishopp, A.; Costa de Oliveira, A.; Courtois, Brigitte; Diedhiou, A.; Diévart, A.; Gantet, P.; Ghesquière, A.; Guiderdoni, Emmanuel; Henry, Amelia; et al. (Springer, 2014)
Rice production faces the challenge to be enhanced by 50% by year 2030 to meet the growth of the population in rice-eating countries. Whereas yield of cereal crops tend to reach plateaus and a yield is likely to be deeply affected by climate instability and resource scarcity in the coming decades, building rice cultivars harboring root systems that can maintain performance by capturing water and nutrient resources unevenly distributed is a major breeding target. Taking advantage of gathering a community of rice root biologists in a Global Rice Science Partnership workshop held in Montpellier, France, we present here the recent progresses accomplished in this area and focal points where an international network of laboratories should direct their efforts.